Action Plan for Stroke in Europe 2018–2030. (December 2018) - Norrving, Bo; Barrick, Jon; Davalos, Antoni; Dichgans, Martin; Cordonnier, Charlotte; Guekht, Alla; Kutluk, Kursad; Mikulik, Robert; Wardlaw, Joanna; Richard, Edo; Nabavi, Darius; Molina, Carlos; et al.
Abstract: Two previous pan-European consensus meetings, the 1995 and 2006 Helsingborg meetings, were convened to review the scientific evidence and the state of current services to identify priorities for research and development and to set targets for the development of stroke care for the decade to follow. Adhering to the same format, the European Stroke Organisation (ESO) prepared a European Stroke Action Plan (ESAP) for the years 2018 to 2030, in cooperation with the Stroke Alliance for Europe (SAFE). The ESAP included seven domains: primary prevention, organisation of stroke services, management of acute stroke, secondary prevention, rehabilitation, evaluation of stroke outcome and quality assessment and life after stroke. Research priorities for translational stroke research were also identified. Documents were prepared by a working group and were open to public comments. The final document was prepared after a workshop in Munich on 21–23 March 2018. Four overarching targets for 2030 were identified: (1) to reduce the absolute number of strokes in Europe by 10%, (2) to treat 90% or more of all patients with stroke in Europe in a dedicated stroke unit as the first level of care, (3) to have national plans for stroke encompassing the entire chain of care, (4) to fully implement national strategies for multisector public health interventions. Overall, 30 targets and 72 research priorities were identified for the seven domains. The ESAP provides a basic road map and sets targets for the implementation of evidence-based preventive actions and stroke services to 2030.